A novel EGFR exon 21 indel mutation in lung adenocarcinoma and response to dacomitinib: A case report. Issue 34 (26th August 2022) - Zhou, Tao; Xiong, Qiang; Hong, Chen; Wang, Qian; Wang, Wenxian; Xu, Chunwei; Cai, Jing
Abstract : Rationale: Uncommon epidermal growth factor receptor (EGFR) mutations are increasingly being identified in non-small cell lung cancer. Insertion and deletion mutations have been detected in exons 18, 19, and 20, but not in exon 21. In patients with uncommon mutations, the second-generation EGFR tyrosine kinase inhibitor afatinib has shown good efficacy, whereas that of dacomitinib, another second-generation EGFR-tyrosine kinase inhibitor, remains unknown. Here, we reported a patient with a novel EGFR21 exon insertion-deletion (indel) mutation and demonstrated the efficacy of dacomitinib. Patient concerns: A 59-year-old nonsmoking Chinese male was admitted to the hospital with lung cancer after a chest computed tomography for coughing and sputum. The patient's condition progressed after multiple treatments including surgery, chemotherapy, and radiotherapy. Diagnosis: The patient had clinical manifestations of cough and sputum and was pathologically confirmed to have T2bN1M0 (stage IIB) lung adenocarcinoma according to the seventh edition of tumor-node-metastasis staging. The patient underwent a second operation after detection of recurrence, and postoperative pathology confirmed adenocarcinoma of the lung. The patient progressed again after surgery, and the tumor-node-metastasis stage was changed to T4N0M1a (stage IVA) before treatment with dacomitinib. Interventions: After detection of the EGFR exon 21 indel mutation, the patient began treatment with dacomitinib (45 mg once a day) on March 12, 2021. Outcomes: After 1 month of targeted therapy, the patient showed a partial response to dacomitinib. As of March 19, 2022, his condition remained stable and he continued to receive dacomitinib. Progression-free survival reached 12.4 months. The patient experienced mild adverse reactions of pruritus during the use of dacomitinib, but recovered after drug treatment. Lesson: We reported a novel EGFR exon 21 indel mutation in a lung adenocarcinoma patient. Dacomitinib showed efficacy in the treatment of a patient with this mutation, suggesting that its efficacy in patients with uncommon mutations should be explored further. The next-generation sequencing is recommended as a guiding tool for the treatment of advanced non-small cell lung cancer.